2021
DOI: 10.1051/bsgf/2021023
|View full text |Cite
|
Sign up to set email alerts
|

Multistage development of a hydrothermal W deposit during the Variscan late-orogenic evolution: the Puy-les-Vignes breccia pipe (Massif Central, France)

Abstract: The Puy-les-Vignes W deposit, located in the northwestern French Massif Central (FMC), is a rare occurrence worldwide of a wolframite-mineralized hydrothermal breccia pipe hosted in high-grade metamorphic gneisses. We present here an integrated study of this deposit aiming to characterize the ore-forming hydrothermal system in link with the Variscan late-orogenic evolution of the FMC. Based on a set of representative samples from the host rocks and mineralization, we describe a detailed paragenetic sequence an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 180 publications
(207 reference statements)
0
2
0
1
Order By: Relevance
“…12) et appuyant une cristallisation à la fin de l'étape magmatique-hydrothermale. Les cassitérites des gisements tardi-hercyniens proches (Montebras, Échassières-Beauvoir, Puy-les-Vignes) possèdent des compositions plus variables, plus riches en Nb et Ta, mais ces gisements montrent plusieurs générations de cassitérite (Monnier et al, 2019 ;Harlaux et al, 2021 ;. Enfin, la gangue à biotite-chlorite et fluorapatite, mais sans topaze ni tourmaline, dénote un magma probablement assez pauvre en fluor et sans bore.…”
Section: Conditions De Formation Du Gisementunclassified
“…12) et appuyant une cristallisation à la fin de l'étape magmatique-hydrothermale. Les cassitérites des gisements tardi-hercyniens proches (Montebras, Échassières-Beauvoir, Puy-les-Vignes) possèdent des compositions plus variables, plus riches en Nb et Ta, mais ces gisements montrent plusieurs générations de cassitérite (Monnier et al, 2019 ;Harlaux et al, 2021 ;. Enfin, la gangue à biotite-chlorite et fluorapatite, mais sans topaze ni tourmaline, dénote un magma probablement assez pauvre en fluor et sans bore.…”
Section: Conditions De Formation Du Gisementunclassified
“…Element distribution maps (e.g., SEM-EDS or µXRF) can be also used to target internal zones, or to exclude samples for ID-TIMS analyses. Near-infrared microscopy (e.g., Ortelli et al 2018;Harlaux et al 2021) and X-ray computed tomography (CT; Harlaux et al 2018a) are also promising tools to investigate the textures of wolframite and to provide 3D information about the relative proportions and the spatial distribution of micro-inclusions and/or alteration zones.…”
Section: Assessment Of Commonmentioning
confidence: 99%
“…New insight has been provided for the timing and duration of Sn±W ore deposit formation via U-Pb dating of ore minerals such as cassiterite and wolframite (e.g., Zhang et al, 2017;Harlaux et al, 2018a;Moscati and Neymark, 2020;Tang et al, 2020;Denholm et al, 2021;Gemmrich et al, 2021;Carr et al, 2021). Importantly, most of the latter studies focused on several mineralized districts whereas there are only a few reported detailed geochronological results that have bracketed the duration of magmatic-hydrothermal events in a single Sn±W deposit (Hu et al, 2012;Chen et al, 2019;Carr et al, 2020;Mohammadi et al, 2020;Tapster and Bright, 2020;Legros et al, 2020;Harlaux et al, 2021a). This paper presents a detailed geochronological study of the San Rafael Sn (-Cu) deposit, one of the world's largest granite-related cassiterite-bearing lode systems, that is located in the Central Andean tin belt of southeast Peru.…”
Section: Introductionmentioning
confidence: 99%